The natural history of primary sclerosing cholangitis in 781 children: A multicenter, international collaboration - Deneau, Mark R.; El‐Matary, Wael; Valentino, Pamela L.; Abdou, Reham; Alqoaer, Khaled; Amin, Mansi; Amir, Achiya Z.; Auth, Marcus; Bazerbachi, Fateh; Broderick, Annemarie; Chan, Albert; Cotter, Jillian; et al. (Hepatology (Baltimore, Md.), 2017)
There are limited data on the natural history of primary sclerosing cholangitis (PSC) in children. We aimed to describe the disease characteristics and long‐term outcomes of pediatric PSC. We retrospectively collected all pediatric PSC cases from 36 participating institutions and conducted a survival analysis from the date of PSC diagnosis to dates of diagnosis of portal hypertensive or biliary complications, cholangiocarcinoma, liver transplantation, or death. We analyzed patients grouped by disease phenotype and laboratory studies at diagnosis to identify objective predictors of long‐term outcome. We identified 781 patients, median age 12 years, with 4,277 person‐years of follow‐up; 33% with autoimmune hepatitis, 76% with inflammatory bowel disease, and 13% with small duct PSC. Portal hypertensive and biliary complications developed in 38% and 25%, respectively, after 10 years of disease. Once these complications developed, median survival with native liver was 2.8 and 3.5 years, respectively. Cholangiocarcinoma occurred in 1%. Overall event‐free survival was 70% at 5 years and 53% at 10 years. Patient groups with the most elevated total bilirubin, gamma‐glutamyltransferase, and aspartate aminotransferase‐to‐platelet ratio index at diagnosis had the worst outcomes. In multivariate analysis PSC–inflammatory bowel disease and small duct phenotypes were associated with favorable prognosis (hazard ratios 0.6, 95% confidence interval 0.5‐0.9, and 0.7, 95% confidence interval 0.5‐0.96, respectively). Age, gender, and autoimmune hepatitis overlap did not impact long‐term outcome. Conclusion: PSC has a chronic, progressive course in children, and nearly half of patients develop an adverse liver outcome after 10 years of disease; elevations in bilirubin, gamma‐glutamyltransferase, and aspartate aminotransferase‐to‐platelet ratio index at diagnosis can identify patients at highest risk; small duct PSC and PSC–inflammatory bowel disease are more favorable disease phenotypes. (Hepatology 2017;66:518–527).